Sexting, sextorsión, doxing y porno venganza como manifestación de violencia contra la mujer en el municipio de Sabanalarga Atlántico 2021-2022 (2022)
The present investigation on Violence against Women in Social Networks by Dissemination of Images without consent in the Municipality of Sabanalarga Atlantico 2021-2022, proposes as a general objective, to analyze violence against women in social networks by dissemination of images without consent and the and the specific ones: Identify the characteristics that describe such violence, describe the normative framework in relation to the regulation of violence against women and propose awareness campaigns. Socio-legal research, under a quantitative approach, applying surveys to collect information from thirty (30) women under Microsoft Forms. As results, characteristics that indicate violence against women in social networks were identified, in order to counteract, control and avoid it, as ascourge against the free, dignified and rights-based human being. In Colombia, the regulatory framework does not contemplate computer crimes due to violence against women, limiting its control. It is possible to propose awareness campaigns against violence against women in networks, to help against damage caused by publications of sexual images without consent: and to carry out educational processes. It is concluded in a type of violence that violates the rights to a full life, the need to include this type of violence in the regulatory framework for defense and protection, the need for awareness campaigns to unite everyone's efforts against this scourge